Dilematika Putusan Mahkamah Konstitusi vs Kekuatan Politik dalam Impeachment Presiden - Nadir Nadir (Jurnal Konstitusi, 2016)
The involvement of the constitutional court of RI in examining and ruling on  the case of presidential impeachment is textually not the authority but obligation that whether or not presidential impeachment happen during president’s terms of office will be determined by the supporting political strength in the MPR session.  The decision taken in the session should be based on the decision of Constitutional Court as the interpreter and the guardian of the constitution. This condition causes Constitutional Court decision becomes dillematic because it will be determined by the political strength in the session of the MPR. Besides,the fact that three of the nine judges are proposed by the President and three other are proposed by DPR is also dilemmatic.